Community Structure and Carbon Content of Mangroves in the Tanjung Batu Sekotong Area in the Middle of West Lombok - Novia Indra Anggraini; Didik Santoso; I Gde Mertha (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The purpose of this research was to determine the community structure and the amount of carbon content and mangrove uptake in the Tanjung Batu Sekotong area, Central Lombok, West Lombok. This type of research is descriptive research. This research was conducted in the Tanjung Batu Sekotong area, Central Lombok, West Lombok. The variables observed were individual mangrove species, mangrove height and trunk diameter at breast height. Then the data obtained were analyzed for density, frequency, cover area, important value index, diversity index, biomass and carbon content. Collecting data on mangrove plant communities used a combined method, namely line and square transects. The research results obtained found 6 species, namely Avicennia alba, Avicennia marina, Rhizophora Apiculata, Rhizophora mucronata, Rhizophora stylosa, and Sonneratia alba. Carbon content and carbon absorption of mangroves in the Tanjung Batu Sekotong Tengah Region, West Lombok. The total carbon content of the tree category is 34.4246 tons C/ha, an average of 5.7374 tons C/ha and the sapling category with a total of 14.4312 tons C/ha, an average of 4.1232 tons C/ha. Mangrove carbon uptake in the tree category with a total of 126.3381 tons C/ha, an average of 21.0564 tons C/ha and mangrove absorption in the sapling category with a total of 52.9625 tons C/ha, an average of 8.8271 tons C/ha.